Knowledge and attitude towards the use of pain medications according to WHO cancer pain analgesic ladder in tertiary care hospitals of Pakistan - Ausaf Ahmed Khan; Ali Sarfraz Siddiqui; Mohsin Nazir Butt; Tanveer Baig; Gauhar Afshan (Journal of the Pakistan Medical Association, 2024)
To assess the knowledge and attitude of practicing physicians and surgeons towards the use of pain medication according to the World Health Organisation cancer pain analgesic ladder, the current study was conducted at tertiary care hospitals of the four provinces of Pakistan. Professionals having experience of treating cancer patients for >2 years were included. Data was collected using a self-administered questionnaire sent to each participant using Google Forms. Of the 630 physicians approached, 133(21%) responded. Of them, 74(55.64%) participants were familiar with the World Health Organisation analgesic ladder. There was a significant difference in the frequency of using the ladder based on age (p<0.05). Most participants 31(23%) reported the non-availability of the recommended drugs as the reason for not following the analgesic ladder. There is a strong need to educate physicians and surgeons about the World Health Organisation analgesic ladder, and to make strategies to improve opioid availability in Pakistan.